The Representation of English and Arabic Para Athletes with Special Reference to Transitivity System - Al-Kaaby, Saad; Al-Zubaidi, Nassier (Al-Adab Journal, 2023)
This article employs one of the tools proposed by Jeffries’ (2010) framework of critical stylistic namely the TCF of representing actions/events /and states (transitivity) to examine how male and female Para Athletes are linguistically constructed as social actors in selected English and Arabic Paralympic sport magazines. It aims to identify the stylistic strategies employed in these selected magazines in their textual representation to construct the identity of Para Athletes and the effect of gender and disability in such representation. The study is focused on the analysis of 10 English articles and 10 Arabic articles from English and Arabic magazines related to the field of Para sport and issued between 2016 and 2020. To achieve the research objectives, the study hypothesizes that both the English and Arabic texts tend to assign agent roles to Para Athletes with varied gender preferences. The results of this study show that the selected magazines activate Para Athletes in an attempt to bring People with disabilities (PWDs) from margin to the foreground as social actors. However, the findings also indicate a differential representation of Para Athletes in terms of gender in that both English and Arabic texts allocate agent roles to Para Athletes, however the English texts portray males mainly as Sensers and Sayers, while the Arabic texts portray females as Actors, Sensers, Carriers, and Sayers more than males. This contradicts the common belief that women's contribution to society is excluded and underestimated, suggesting that they can play an important functional role in society like men, regardless of their social status.